Феномен сексуальной объективации в видеоиграх - Одегова, Е. А. (ХНУРЕ, 2019)
The relevance of the topic is confirmed by the great influence of the gaming industry and the development of graphies capabilities. The social significance of this topic is indicated. The concept and the problems of sexual objectification in games are defined. Conclusions were made about possible changes in the gaming industry, reducing objectification.